Volatile Organic Compound Emissions From Heated Synthetic Hair: A Pilot Study - Donna Auguste; Shelly L Miller (SAGE Publishing, 2020)
Volatile organic compounds (VOCs) are emitted from a variety of household and personal care products. Many VOCs are known to be potentially toxic or carcinogenic. Synthetic hair is used in hair-styling practices, including practices in African American communities that involve singeing or heating the synthetic hair. The research questions that we sought to answer were as follows: Are VOCs emitted from singed or heated synthetic hair? If so, what are the VOC species and relative masses identified in singed or heated synthetic hair? We tested samples from 2 sources of singed and heated synthetic hair in a microchamber; one source was flame-retardant synthetic hair and the other source was non-flame-retardant synthetic hair. Our findings confirmed that VOCs are emitted from singed or heated synthetic hair for both types of sources. For flame-retardant synthetic hair, we identified and measured mass for species that included acetone, acetonitrile, 2-butanone, benzene, chloromethane, chloroethane, and 1,2-dichloroethane. For non-flame-retardant synthetic hair, we identified and measured mass for species that included acetone, acetonitrile, chloromethane, trichlorofluoromethane, and 2-propanol.